Italianization Accomplished - Carelli, Paolo (VIEW Journal of European Television History and Culture, 2014)
After the fall of the Berlin Wall and the end of communist regimes in 1989, national media systems of the Eastern European countries belonging to the Soviet bloc began a process of transformation along the way of liberalization and commercialization. In Albania, this process occurred in different phases, but with a common trend, that is the Italian television as a structural, economic and cultural model to inspire. In this article, I try to outline the deep influences and legacies between Italian and Albanian television systems (dating back to the last years of the regime) showing how, despite a progressive sliding towards americanization, they remain a typical landmark of Albanian media. From the formats of the first programmes after the regime to the recent appearances of Italian Tv presenters (in particular, from Berlusconi's channels) on Albanian private channels, we can observe a subtle but rooted and continuous dependency from the country on the other side of the Adriatic Sea.